Molecular and cellular changes in Atlantic halibut (Hippoglossus hippoglossus) skin during metamorphosis - Alves, Ricardo Nuno Henriques Graça (2018)
Metamorphosis in vertebrates is driven by thyroid hormones (THs) and in flatfish consists in the extraordinary transformation of a symmetric pelagic larva into an asymmetric benthic juvenile. The mechanisms underlying how THs can orchestrate the cellular, morphological and functional modifications associated with maturation of juvenile/adult states in flatfish are still unexplored. The Atlantic halibut (Hippoglossus hippoglossus) was the target of the present thesis and the molecular basis of THs action was determined in the head, skin and gastrointestinal tract using RNA sequencing. The first objective of the present thesis was to generate reference transcriptomes of these three tissues using 454 pyrosequencing. Transcriptome dynamics during metamorphosis were mapped with SOLiD sequencing of whole larvae and revealed greater than 8,000 differentially expressed (DE) genes significantly up- or down-regulated in comparison with the juvenile stage. The present study contributes substantially to the molecular resources available for this species and will be an important tool for identifying new potential molecular markers for solving problems related to Atlantic halibut production during metamorphosis. The second part of this thesis was focused in the skin due to its importance as the major barrier between the animal and its external environment and the involvement of THs in skin development during metamorphosis has been described. The present work targets the development of the primary barrier, osmoregulatory capacity and pigmentation development of Atlantic halibut skin. A multivariate approach using bioinformatics, biochemistry and molecular biology techniques allowed the characterization of the asymmetric development of H. hippoglossus ocular and abocular skin sides. The asymmetric development of skin is associated with metamorphosis although establishment of its primary barriers and osmoregulatory functional properties occurs early and is independent of metamorphosis. In addition, it was hypothesized that thyroid axis has a central role in the asymmetric pigmentation observed during metamorphosis in ocular and abocular skin sides. The third part consisted in study the cross-talk between the thyroid and cortisol axis and it was observed that both THs and cortisol act synergistically in modulating the changes in skin during halibut metamorphosis.